Komunikační strategie pro společnost Monsanto, s.r.o. - Mikulcová, Jana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce se zabývá zpracováním komunikační strategie pro společnost Monsanto s.r.o. zabývající se zemědělskými produkty. Práce popisuje obecné a oborové okolí společnosti, společnost samotnou a na základě těchto analýz navrhuje efektivní komunikační strategii.

Master`s thesis concerns the design of a communication strategy for agricultural products company Monsanto Ltd. This work describes the general and field specific context of the company and the company itself, then uses this analysis as the basis for the design of an effective communication strategy.
Communication Strategy for the Company Monsanto, Ltd.
Keywords: marketing; marketingová komunikace; komunikační strategie; komunikační kanály; zákazník; marketing; marketing communication; communication strategy; communication channel; customer